NON DEBT TAX SHIELD, BIAYA CSR, KOMISARIS INDEPENDEN, KOMITE AUDIT DAN TINDAKAN PENGHINDARAN PAJAK OLEH BANK YANG TERDAFTAR DI BEI - Nuraini, Nuraini (UNIB Press, 2019)
This study aims to find empirical evidence on the influence of non-debt tax shield, corporate social responsibility costs, independent commissioners and audit committees on corporate tax avoidance measures. Population in this study are all banking companies listed on the Stock Exchange 2011-2015. The type of research used in this study is empirical research. The sampling technique used is purposive sampling. Based on sampling through purposive sampling, then obtained as many as 30 samples of banking companies with a total of 89 research observations. The results of this study found that non-debt tax shield, independent commissioners and audit committee have a positive effect on tax avoidance measures. While the cost of corporate social responsibility negatively affect the action of tax evasion company.